Role of fluorescence imaging device in screening of oral cancer: A cross-sectional study in chhattisgarh population - Shilpa Jain; Kamlesh Jain; Priyamvada Singh Bais; Swapnil V Shinkar; Fatema Saify (Wolters Kluwer Medknow Publications, 2021)
Background: Oral squamous cell carcinoma is a major health issue worldwide. Screening and early diagnosis are the key elements for the better prognosis of potentially malignant oral disorders. Objectives: This study establishes the effectiveness of fluorescence imaging device in the early detection and precise examination of the normal-appearing oral mucosa of tobacco chewer patients in white light and fluorescence light. Materials and Methods: The study consists of a total of 150 patients equally categorized into frequent tobacco chewers with normal mucosa, precancerous lesion, and cancerous lesion. Out of which 10 cases were excluded due to technical errors and consent-related issues. The correlation between examined oral mucosa under white light and fluorescence light was evaluated through a 2 × 3 contingency table Chi-square test. Results: Out of 140 participants with a positive cancer diagnosis, there are 43 and 53 patients were sensitive to white light andfluorescence light, respectively. The estimated values for sensitivity and specificity were 0.83 (95% confidence interval: 0.736-0.906) for biopsy report diagnosis. Conclusions: Although autofluorescence device plays a critical role in the diagnosis of precancerous oral mucosal lesions in the early stages, the histopathological evaluation remains the gold standard diagnostic approach for this life-threatening disease. Due to the high sensitivity of autofluorescence examination, it has a vital role in determining high-risk oral lesions (precancerous) and oral cancer in mass screening programs for the cancer-prone population.